Security Risk Analysis in Accounting Information Systems Based on Data Dashboard from the Palo Alto Network PA-820 UTM - Roup, Abdul (LPPM Institut Bisnis dan Informatika Kesatuan, 2024)
This study analyzes security risks in accounting information systems using data from the Palo Alto Network PA-820 UTM dashboard, which monitors various aspects such as network activity, user activity, and application usage. The data includes information on data transfers, source and destination IP activities, and system rule usage. The study aims to identify potential threats that could affect the integrity and security of accounting information systems. Keywords: Accounting Information Systems, Security, Risk, Dashboard, Network Activity.